2015
DOI: 10.1016/j.metabol.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Lipopolysaccharide Modulate Mitochondrial Oxygen Consumption in Skeletal Muscle

Abstract: Objective We have previously demonstrated that activation of toll-like receptor 4 (TLR4) in skeletal muscle results in an increased reliance on glucose as an energy source and a concomitant decrease in fatty acid oxidation under basal conditions. Herein, we examined the effects of lipopolysaccharide (LPS), the primary ligand for TLR4, on mitochondrial oxygen consumption in skeletal muscle cell culture and isolated mitochondria. Materials/ methods Skeletal muscle cell cultures were exposed to LPS and oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 64 publications
7
32
0
Order By: Relevance
“…1). Although reduced maximum respiration has been described recently for LPS exposure (21), the increase in basal respiration in our investigation is unique for the HS stimulation. These findings may be partly explained by the role of soluble HS as an endogenous danger-associated molecule (22).…”
Section: Heparan Sulfate Alters Myocardial Mitochondrial Functionmentioning
confidence: 56%
“…1). Although reduced maximum respiration has been described recently for LPS exposure (21), the increase in basal respiration in our investigation is unique for the HS stimulation. These findings may be partly explained by the role of soluble HS as an endogenous danger-associated molecule (22).…”
Section: Heparan Sulfate Alters Myocardial Mitochondrial Functionmentioning
confidence: 56%
“…According to the reverse Randle cycle, it is possible that the LPS induced rise in circulating FFA could reduce glucose uptake and oxidation without impairing insulin signaling 78, 79 . These observations are in contrast to a switch to preferential glucose oxidation over fatty acid oxidation in the fasting period in rodent skeletal muscle following acute LPS exposure 41, 42 . However it is important to note that these studies use different LPS dosing paradigms, therefore the continuous infusion of LPS over 360 minutes in the former study 75 may alter skeletal muscle metabolism differently than a single LPS injection or short LPS exposure 41, 42 .…”
Section: Metabolic Endotoxemia and Obesity: Evidence In Humansmentioning
confidence: 61%
“…This data suggests that the metabolic perturbations in skeletal muscle are due, at least in part, to NFκB translocation via LPS-TLR4 activation. Follow-up studies in C2C12 cells demonstrated decrements in mitochondrial respiration following short-term (2 hour), low dose (50 pg/mL) LPS treatment 42 . In addition, co-treatment with LPS and the antioxidant, n-acetyl-cysteine (NAC), prevented changes in cellular mitochondrial respiration and changes in basal substrate metabolism previously reported (Figure 2A–D).…”
Section: Metabolic Endotoxemia and Obesity: Evidence In Rodentsmentioning
confidence: 94%
See 1 more Smart Citation
“…Mitochondria were isolated as previously described from ~ 75 -100 mg of red skeletal muscle 13 . Between 5 -10 µg/µl of mitochondrial protein will be attained from this amount of tissue by resuspending the final mitochondrial pellet in ≤50 µl of isolation buffer for mitochondria (IBM) 2 (See Frisard et al (Table 3) and injections (Table 4-5) and adjust pH as desired (pH 7.4).…”
Section: Protocolmentioning
confidence: 99%